Subaltern Resistance to Epistemic Violence and Patriarchal Oppression in R.F Kuang’s The Poppy War - Latifa Maharani Gunawan; Ruly Indra Darmawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes how patriarchal structures and epistemic violence silenced and marginalized Rin as a subaltern woman in R.F. Kuang’s novel The Poppy War. Her efforts to resist these systems reflect the subaltern voice through the lens of Gayatri Spivak’s postcolonial feminism. Even though postcolonial feminist scholars have begun paying attention to fantasy literature, Spivak’s ideas have rarely been used to analyze this novel, leaving a significant gap in our understanding of how fantasy can portray the silencing of marginalized women. This study applies a descriptive qualitative approach and close reading to explore how the novel brings ideas to life. The findings reveal that Rin is oppressed by the patriarchal structure and epistemic violence working together, not individually. Supporting Spivak’s (1988) argument that subaltern women cannot truly speak in their own right because the dominant system never allows their voice to be heard on their own terms, Rin’s resistance is quietly reshaped by those in power. As one of the first studies to directly apply Spivak’s framework to The Poppy War, this research strengthens postcolonial feminist studies by demonstrating that fantasy literature can serve as an unexpectedly strong space for understanding how marginalized women speak, resist, and are subsequently silenced.